SIMULASI KUALITAS LAYANAN VOIP MENGGUNAKAN METODE ANTRIAN PAKET CBQ DENGAN MEKANISME LINK SHARING - Agoes, Suhartati; Putranto, Adi (Jurnal Teknik Elektro, 2007)
Main problem faced by Voice over IP service is the level of delay and packet loss yielded.Queue delay that happened when packet enter router interface have a big effect in real-timecommunications like Voice over Internet Protocol (VoIP). First In First Out (FIFO) QueueSystem does not own arrangement to traffic passing through it, all packets assumed equal. IfVOIP packets queue up together with data packet at this system hence the delay yielded willbe very big. A correct queue method needed to improve network delay characteristic andimprove Quality of Service (QOS) of VoIP. One QOS management method on VoIP which canbe used is CBQ (Class Based Queuing) queue method. CBQ represent scheduling mechanismproviding link-sharing among classes using same physical link. This is the method enabledivision of bandwidth allocation from router output port as according to traffic type andpriority. In the event of congestion, traffic with high priority will accept minimum bandwidthallocations as which have previous reservation. At the simulated scenario and networktopology, CBQ queue method able to meet the requirement of maximum delay according toITU recommendation G.114. Based on calculation conversion R factor value to MOS by usingE-Model, CBQ can assign MOS value more than 4 (four), meaning its value is good. So thatVoIP service is competent to be implemented.Keyword: Bandwidth, CBQ, FIFO, link-sharing, MOS